Saúde e ambiente na gestão ambiental pública das unidades de conservação da natureza : uma análise das práticas discursivas sobre as concessões em parques e florestas nacionais do Brasil - Estevão, Priscilla Correa de Moura (2023)
The deconstruction of socio-environmental management in Brazil and the privatization of common goods, traditional territories and protected natural areas are recorded in national administrative acts. The recent concession projects have strengthened the commitment to the economic exploitation of parks and forests, which are federal assets and are being commodified as natural assets in the financial system. The Federal Government's privatization program, in addition to offering the private sector the concession of services, areas or facilities in Nature Conservation Units for the exploitation of visitation, recreation and tourism activities, allows for the private funding of actions to support the conservation, protection and management of federal Conservation Units, and the granting of the right to market carbon credits and environmental services to the private sector. The subject under investigation is in the area of environmental health in the field of Collective Health and problematizes the universalization of access to and use of public spaces, goods and services interrelated to the health and environmental sectors. The purpose of this research was to analyze the role played by the state in the decision-making process regarding concessions in federal Conservation Units in a context of commercialization and dismantling of the public environmental management model. The methodology used was a qualitative approach based on documentary analysis combined with methodological procedures for analyzing discursive practices. Bibliographic resources and nonarchived public domain documents were the sources for the research data. With the elucidating mechanism of the parks-merchandise category forged by Mascario's thinking, the results show that the partnership between BNDES and the Semeia Institute guided the public management of biodiversity towards contracting consortia or private companies for concessions in national parks and forests. The investigation shows that the processes of reviewing the management plans of the Conservation Units have been instrumentalized, that the concession processes lack greater transparency and participation by society at local level, and that the absence of participatory management and effective dialogue with the management councils of the federal Conservation Units has led to a great concentration of decision-making power in the top government positions, secretariats and ministries.